(untitled) (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This article analyzes the impact of economic conflicts and sanctions on prices and demand in the global market. It discusses the role of sanctions in the global economy, how they affect goods and services markets, and the changes in prices and demand that arise in the global economic environment. The article also examines how economic conflicts, trade wars, and sanctions affect trade relations between countries, competitiveness, and global economic growth. Based on the analyzed data, the article highlights the positive and negative aspects of sanctions and economic conflicts, as well as the necessary measures to reduce their impact on prices and demand in the global market.